Evaluasi Manual Material Handling (MMH) Di Gudang BULOG Ngabeyan Surakarta Menggunakan Metode Multitask Job Analysis dan Fisiologi - Pratiwi, Okta Indah Dwi, Ir. Etika Muslimah,ST.MM.MT (2016)
Manual Material Handling (MMH) is still founded in Indonesia. Handling the job with that way is giving the high risk in work accident. The instance which used Manual Material Handling (MMH) is BULOG storage Ngabeyan Surakarta. All processing in that storage, from the commodities are arrived until distributing is still manually. Many employees complaining the effect of MMH, one of them is painful. Therefore, NIOSH makes a method named Recommended Weight Limit (RWL) to determining the maximum weight which can lifted by the employees and determining the job is recommended or not. RWL is divided becomes two types by NIOSH, there are single task job analysis and multitask job analysis. Because of the type of job in BULOG is a type of job with horizontal, vertical and pile that different, then using multitask job analysis. If it was get the RWL value, and LI, then can discovered the value of Composite Lifting Index. If CLI > 1, it means the job is not recommended. In other hand, pules or heart beats from the employees are the important thing to analyzing, besides multitask job analysis aspect, the research also will be seen from physiology aspect to determining energy expenditure (EE) of the employees. The result of this research established that from three employees who measured is getting CLI value there are 13.611, 16.182 and 15.140. Based on the value CLI > 1, it means the load of physical work which accepted by the employees is so high and it is not recommended, and can risk of injury like Cumulative Trauma Disorder (CTD) and osteoarthritis. The result from physiology aspect established that EE from three of employees is 5.63 Kcal/minute, 5.81 Kcal/minute and 5.63 Kcal/minute, that value is categorized as difficult job. Therefore, from two aspects, all of them established a result that the job can giving the high load of physical and risked. Keywords: CLI, Energy expenditure, Physiology, MMH, Multitask job analysis